Development of Problem-Based Learning Activities Integrated with Real-Life Mathematics Education Concepts on Ordinary Differential Equations to Enhance Problem-Solving Skills for Students at Roi Et Rajabhat University - Mingolo, Narintra (Ratchaphruek Journal, 2025)
This research was a study the effectiveness of problem-based learning (PBL) activities integrated with real-life mathematics education concepts to enhance mathematical problem-solving skills. The study aimed to: 1) Develop and determine the effectiveness; 2) Compare students’ mathematical problem-solving abilities before and after the activities; and 3) Study students’ satisfaction with the PBL activities. The sample consisted of 29 students enrolled in Calculus II during the second semester of the 2023 academic year at Roi Et Rajabhat University. The research instruments included PBL activities integrated with real-life mathematics concepts, a mathematical problem-solving test, and a satisfaction questionnaire. Data were analyzed using mean, standard deviation, and dependent sample t-test. The findings revealed that: 1) the PBL activities were highly appropriate and effective with an efficiency score of 85.10/80.34, which is higher than the set standard of 75/75; 2) students’ post-learning mathematical problem-solving abilities were significantly higher than their pre-learning abilities at the .01 level; and 3) students’ overall satisfaction with the PBL activities was at the highest level.